1964
DOI: 10.1113/jphysiol.1964.sp007464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sodium deprivation and loading on the plasma‐renin in man

Abstract: The mechanisms controlling the secretion of aldosterone are incompletely understood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 46 publications
2
46
0
1
Order By: Relevance
“…S., the amount of sodium excreted was 2-3 meq/day less than the measured amount of sodium ingested ( Fig. 1; Table IV), a characteristic occurrence in normal subjects during dietary restriction of sodium (23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…S., the amount of sodium excreted was 2-3 meq/day less than the measured amount of sodium ingested ( Fig. 1; Table IV), a characteristic occurrence in normal subjects during dietary restriction of sodium (23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies in the nephrectomized rat (N = 3) had shown that this dose of inhibitor reduced the angiotensin I pressor response initially to 17%; after 60 minutes the response was still only 1 Generously supplied by Dr. R. A. Vukovick of the Squibb Institute.…”
Section: Methodsmentioning
confidence: 99%
“…A reciprocal relationship between plasma renin activity and sodium balance has been well documented (1,2). Thus, sodium depletion stimulates renin secretion, and sodium loading suppresses renin release.…”
mentioning
confidence: 99%
“…Katsuyoshi Kudoh 1) , Chikashi Shibata 2) , Yuji Funayama 3) , Kouhei Fukushima 4) , Kenichi Takahashi 5) , Munenori Nagao 1) , Sho Haneda 5) , Kazuhiro Watanabe 1) , Takeshi Naitoh 1) and Michiaki Unno 1)…”
Section: Oral Rehydration Solution Normalizes Plasma Renin and Aldostmentioning
confidence: 99%
“…Dehydration and sodium deprivation induce hypersecretion of renin from the juxtaglomerular apparatus in the kidney [4][5][6] . Renin finally increases the secretion of aldosterone and the antidiuretic hormone vasopressin via the angiotensin pathway.…”
Section: Introductionmentioning
confidence: 99%